Exploring the roles and practices of libraries in prisons : international perspectives - Garner, Jane (Advances in librarianship ;, 2021)
Over the past fifty years, only a small body of knowledge has been published regarding libraries in prisons. Exploring the Roles and Practices of Libraries in Prisons: International Perspectives aims to strengthen and expand this body of knowledge, with each -- Chapter addressing different aspects of the roles and practices of library services to prisons and prisoners. Writing from Croatia, Sri Lanka, Scotland, Northern Ireland, Australia, Norway, Germany and the United States of America, this edited collection focuses on prison library programming, the role of prison libraries as supporters of prisoner literacy development, censorship, future visions for prison libraries, and descriptions of prison libraries across the world. Libraries in both adult and juvenile prisons are studied, as are prison libraries from diverse carceral contexts such as the rapidly expanding American carceral system, through to the 'normalisation' prisons of Norway. This book will be of interest to prison managers, education and custodial staff, prison librarians, library and information studies academics and students, education researchers and practitioners, readers interested in social justice, education, censorship, prison life, and prison reform.